(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
Interest in the motivational aspect of learning a foreign language has increased significantly in recent years in all disciplines related to language in one way or another not only in psychology and pedagogy, but also in linguodidactics, methods of teaching foreign languages at school, and psycholinguistics. In order to properly adapt to the current situation, when Europe becomes a single multinational, multicultural and multilingual whole, representatives of society at all its levels must realize the importance of learning foreign languages, since the study of languages is a way to foster tolerance, the ability to cooperate, to achieve mutual understanding between peoples, respect for the individual regardless of his race, national, religious, political affiliation.